Comparison of climate change vulnerability assessments for wildlife. (6th January 2014) - Lankford, Amber J.; Svancara, Leona K.; Lawler, Joshua J.; Vierling, Kerri
ABSTRACT The need for wildlife climate change vulnerability and sensitivity assessments has increased over the past decade. Use of these assessments by wildlife and land managers has increased due to concern for potential effects of climate change on species and landscapes. Although many approaches exist for assessing sensitivity and vulnerability to climate change, little is known about the similarity of results between methods. We compared outputs of 3 widely available assessments for the western United States: the NatureServe Climate Change Vulnerability Index, the U.S. Forest Service System for Assessing the Vulnerability of Species, and the Climate Change Sensitivity Database. We performed a broad categorical comparison and examined correlations across rankings to compare assessment outputs. We found little agreement in species rankings between pairs of assessments. There is no apparent pattern within, or between, taxa or habitat associations that could explain this poor correlation. Disparities likely result from differences in question format, choice of data input, or how vulnerability or sensitivity is calculated. Consideration of vulnerability quantification is needed, particularly regarding species sensitivity and adaptive capacity, because of limited understanding of species and community responses to climate exposure. Our results indicate it is extremely important to be aware of the specific goal and the quality, quantity, and variety of data used in each individual assessment in order to adequately use these assessments as tools for management planning. With the increasing need to include climate change scenarios in management actions and decisions, we suggest that increased cooperation among assessment developers could greatly aid in eliminating this discrepancy. © 2014 The Wildlife Society